A Video-Assisted Flipbook-Based E-Module to Enhance Mathematical Critical Thinking Skiils - Thea Suci Wulandari; Rizki Wahyu Yunian Putra; Abi Fadila (Kognitif: Jurnal Riset HOTS Pendidikan Matematika, 2026)
Mathematical critical thinking ability is one of the important competencies in mathematics learning that must be possessed by 21st-century students. However, the results of the study indicate that students' mathematical critical thinking ability is still low and the teaching materials used are less varied, so that learning is less than optimal. Therefore, this study aims to develop a video-assisted flipbook-based e-module to improve mathematical critical thinking ability. This study uses the Research and Development (R&D) method with the ADDIE model which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The subjects of the study were eighth-grade students at SMP Negeri 1 Sidomulyo, with classes selected using the Cluster random sampling technique. Data were collected through interviews, validation questionnaires, interestingness questionnaires and tests with a One Group Pretest-Posttest design. The test instrument was compiled based on indicators of critical thinking ability which include interpretation, analysis, evaluation, and inference. The results of the feasibility test by the material expert validator were 3.73, and the media expert validator were 3.37 with the criteria of "valid". The students' responses in the small group test were 3.39 and the large group 3.48 with the criteria of "very interesting". The N-Gain result of 0.72 with the category of "high" and the effect size of 0.74 with the category of "moderate" indicates that the e-module is effective and has a strong influence in improving mathematical critical thinking skills. Thus, the video-assisted flipbook-based e-module is feasible, interesting, and effective in improving mathematical critical thinking skills.